Proceedings of the BioNLP 2018 Workshop 2018
DOI: 10.18653/v1/w18-2319
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Developing and Evaluating Word Embeddings of Drug-named Entity

Abstract: We investigate the quality of task specific word embeddings created with relatively small, targeted corpora. We present a comprehensive evaluation framework including both intrinsic and extrinsic evaluation that can be expanded to named entities beyond drug name. Intrinsic evaluation results tell that drug name embeddings created with a domain specific document corpus outperformed the previously published versions that derived from a very large general text corpus. Extrinsic evaluation uses word embedding for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…One straightforward approach is to get more labeled data containing entities mentioned above to train our model. Zhao et al [44] showed that training on a specific domain dataset provided better performance than training on a large, general domain dataset. Moreover, using more Chinese clinical corpus to train the Bert-based embedding may be another way to improve the recognition performances of long and complex entities.…”
Section: Discussionmentioning
confidence: 99%
“…One straightforward approach is to get more labeled data containing entities mentioned above to train our model. Zhao et al [44] showed that training on a specific domain dataset provided better performance than training on a large, general domain dataset. Moreover, using more Chinese clinical corpus to train the Bert-based embedding may be another way to improve the recognition performances of long and complex entities.…”
Section: Discussionmentioning
confidence: 99%
“…Seok et al used CRF as a learning algorithm and applied word embedding feature for NE extraction purpose [44]. A few other NER tasks which used word embedding for identifying names were [45][46][47]. There are multiple embedding techniques like 'Word2Vev', and 'GloVe 13 ' etc.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, there has been extensive work to leverage biomedical and clinical texts to develop word embeddings [27]. For example, clinical word embeddings have been trained to identify drugs [28], substance abuse terms [6], and anatomical locations [13]. More recently, word embeddings have been used to understand the COVID-19 pandemic.…”
Section: Covid-19 and Word Embeddingsmentioning
confidence: 99%